2022
DOI: 10.1002/ijc.34166
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRI plus BEvacizumab or aFLIbercept after FOLFOX‐bevacizumab failure for COlorectal cancer (BEFLICO): An AGEO multicenter study

Abstract: Some preliminary data have been published as meeting abstract in Annals of Oncology (D435P).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Torregrosa et al. 29 demonstrated that FOLFIRI-bevacizumab combination was associated with better survival after failure of first line FOLFOX-bevacizumab for mCRC. In short, standard chemotherapy in CRC plays the pivotal role despite the availability of different targeted approaches or immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Torregrosa et al. 29 demonstrated that FOLFIRI-bevacizumab combination was associated with better survival after failure of first line FOLFOX-bevacizumab for mCRC. In short, standard chemotherapy in CRC plays the pivotal role despite the availability of different targeted approaches or immunotherapy.…”
Section: Discussionmentioning
confidence: 99%